Kinetics of ultrasound pretreated apple cubes dried in fluidized bed dryer. Issue 10 (1st July 2020) - Galvão, Andressa M. M. T.; Rodrigues, Sueli; Fernandes, Fabiano A. N.
Abstract: This work evaluated the effect of ultrasonic pretreatment on the production of dehydrated apples ( Malus domestica L. var Granny Smith) in a fluidized bed dryer. Cube-shaped apple samples were subjected to ultrasound in an ultrasonic bath and dried in a fluidized bed drier. The experimental design evaluated the effect of ultrasound pretreatment time (0 to 30 min) on the soluble solids loss during pretreatment and on the drying time. The ultrasonic pretreatment was carried out in a bath ultrasound operating at 25 kHz and outputting 55 W/m 3 of power density. Distilled water was applied in the pretreatment to produce low-calorie apple cubes. Fluidized bed drying was carried out at 30, 40, and 50 °C. Fick's law was used to model the drying process and to determine the apparent water diffusivity. The soluble solid loss ranged between 8.7 and 21.2% during the pretreatment, and the apparent water diffusivity during air drying ranged from 1.09 × 10 −6 to 2.81 × 10 −6 m 2 /min. Ultrasound pretreatment increased the apparent water diffusivity up to 58%. Apple cubes subjected to 20 min of ultrasound pretreatment and dried at 50 °C presented the highest apparent water diffusivity and dried to achieve a water activity of 0.4 in 100 min.